Kajian Literatur: Pemanfaatan TikTok dalam Meningkatkan Pemasaran Produk UMKM - Harsono, Eko; Ariyani, Nafiah (Jurnal Nasional Manajemen Pemasaran dan SDM, 2025)
This study aims to identify effective digital marketing strategies for Micro, Small, and Medium Enterprises (MSMEs) through the TikTok platform. As the digital landscape evolves, TikTok has emerged as a powerful marketing tool that enables MSMEs to reach broader audiences through short-form video content that is interactive, creative, and tailored to user interests. Utilizing a Systematic Literature Review (SLR) approach, this study analyzes six relevant articles published between 2020 and 2025 to evaluate TikTok’s role in enhancing brand visibility, increasing consumer engagement, and boosting product sales. The findings indicate that marketing success on TikTok is strongly influenced by the use of relevant and engaging content, collaboration with influencers, active audience interaction, and optimal utilization of platform features such as live streaming, duet videos, hashtag challenges, and TikTok Shop. These strategies not only attract consumer attention but also foster emotional connections and brand loyalty. While account reputation may support user engagement, it is not the primary factor influencing the intention to follow an MSME account, as quality content and interactivity are more decisive. This study contributes to the growing body of knowledge on social commerce by highlighting the importance of adapting marketing approaches to align with digital consumer behavior. The insights gained are expected to guide MSME practitioners in formulating adaptive and practical digital strategies to thrive in the current digital economy.